Learning algorithms for anomaly detection from images - Ahmed, Tarem; Pathan, Al Sakib Khan; Ahmed, Supriyo Shafkat (© 2017 IGI Global, 2018)
This book chapter was published in the IGI Global [© 2017 IGI Global] and the definite version is available at : http://doi.org/10.4018/978-1-5225-0983-7.ch013 The Journal's website is at: https://www.igi-global.com/gateway/chapter/164608